Technological aspects of vegetable oils transesterification with ethanol in the presence of metal oxides - Melnyk, Yuriy (Array, 2020)
Transesterification of vegetable oil with ethanol in the presence of fine metal oxide particles as catalysts has been investigated. Zinc and nickel(II) oxides were shown to have the highest catalytic activity. In their presence, the conversion of sunflower oil triglycerides, after 150 min, reached 95.3 and 94.2 %, respectively. The optimal mass fraction of zinc oxide catalyst was found to be 0.25–0.31 %. In the presence of zinc oxide, with mass fraction of water in ethanol of 5 and 10 %, the conversion of triglycerides was 98.5 and 94.8 %, respectively.